Oxidation Of Fe(II) By Molecular Oxygen In The Presence Of Fe(OH)3 Surfaces And Elevated Carbonate Concentrations: Consequences For Passive Mine Water Treatment (Society for Mining, Metallurgy & Exploration, 2006)
Current design guidelines for the surface catalysed oxidation of Fe(II) on Fe(OH)3 (Ochre) in passive mine water treatment systems are based largely on empirical data as the details of rates and mechanisms have not fully been revealed. Also the effects of elevated carbonate concentrations, typical of many UK minewaters, on the surface catalysed oxidation rate are unclear. In order to move away from empirical design and towards sound engineering that is based on geochemical and hydrological understanding it is necessary to quantify these reaction rates. In this study the effects of Fe(OH)3 and carbonate on the rate of Fe(II) oxidation by dissolved oxygen have been investigated with an aim to delineate the reaction mechanism. Experiments were conducted under well-controlled conditions. Preliminary results indicate that the surface catalysed reaction is an order of magnitude faster at pH ~6.4 with 200 mg/l Fe(OH)3 than the homogeneous rate and is dominated by an elevated rate of removal and oxidation of Fe(II) from the solution phase. It is also apparent that the oxidation rate of actual adsorbed Fe(II) is substantially retarded with respect to the homogeneous rate. Carbonates were not shown to affect the surface rate within the bounds of this preliminary study.